Analisis Deiksis pada Novel Sa'atu Al-Baghdad Karya Shahad Al-Rawi - Hazzlah, Arlidiyah; Mawardi, Mawardi; Mardiansyah, Yadi (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to explore the use of deixis of persona, time, and place in the novel Sa'atu Al-Baghdad by Shahad Al-Rawi. Understanding the use of deixis in Arabic literary works helps prevent misunderstandings in communication in the Arab world. This research is a qualitative research. The approach used in this research refers to the theory of deixis according to George Yule, which includes persona deixis, time deixis, and place deixis. Data collection in this research uses the listening method followed by note-taking technique. Data analysis technique in this research uses content analysis method. The result of this research shows the forms of deixis in Sa'atu Al-Baghdad novel by Shahad Al-Rawi such as persona deixis, time deixis, and place deixis. In persona deixis, there are uses such as (me), (us), (you women), (you guys), (him), and // (them), which describe the relationship between characters and their position in the story. Time deixis includes words like (a little later), (that day), and (sometimes), which provide a clear temporal orientation in the narrative. Meanwhile, place deixis includes (below), (there), (in front), (above), (here), and (here), which enriches the depiction of the story setting. The use of deixis in this novel serves not only as a linguistic element, but also as an effective pragmatic tool to build narrative depth, emotional connection, and relevant cultural context for readers. This research provides new insights in understanding the role of deixis in Arabic literary works and its importance in intercultural communication.